Gender, entrepreneurship and coping with the COVID-19 pandemic: The case of GoFood Merchants in Indonesia - Yesim Elhan-Kayalar; Yasuyuki Sawada; Yana van der Meulen Rodgers (Asian Development Bank Institute (ADBI), 2022)
This paper examines business performance and crisis mitigation strategies among micro-, small-, and medium-sized enterprises (MSMEs) in Indonesia during the COVID-19 pandemic. We utilize a new primary data set based on administrative records, survey data, and follow-up interviews with merchants using the digital application GoFood, an on-demand cooked food delivery service. Three empirical findings emerge: First, the overall employment size of women-owned businesses shrank more than men-owned businesses after the pandemic outbreak; second, women were more likely than men to cut personal expenditures and use government assistance as crisis mitigation strategies; and third, competition increased sharply as new merchants entered the platform, with service areas of both incumbents and entrants shrinking over time. These results have implications for policies on women's entrepreneurship, the uptake of business development services, and financing programs for MSMEs.
Keywords: J16; J21; O12; L11; 330; women; e-commerce; COVID-19; digitalization; MSMEs